1977
DOI: 10.1530/jrf.0.0510137
|View full text |Cite
|
Sign up to set email alerts
|

A possible role of a specific uterine fluid peptidase in implantation in the rat

Abstract: Although the accumulation of uterine fluid during pro-oestrus in the rat has been well documented (Long & Evans, 1922;Warren, 1938), its exact role in the reproductive process is still not clearly understood. Joshi, Yaron & Lindner (1970) isolated and characterized an endopeptidase from the uterine luminal fluid of pro-oestrous rats and from immature rats treated with oestrogen. This enzyme was later found to be unique to the uterine fluid and was not found in blood (Joshi & Murray, 1974). A protein immunologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…The identity of the zona lysin remains an enigma; it may be secreted in active form or as a proenzyme to be activated by embryonic enzymes as proposed by Denker & Hafez (1975). Joshi & Murray (1974) and Rosenfeld & Joshi (1977 have implicated an oestrogen-dependent rat uterine-specific endopeptidase in zona lysis. Hoversland & Weitlauf (1981, 1982 have observed that the incidence of zona lysis in ovariectomized mice treated with oestradiol and progesterone follows a pattern similar to changes in concentrations of a uterine chymotrypsin-like enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…The identity of the zona lysin remains an enigma; it may be secreted in active form or as a proenzyme to be activated by embryonic enzymes as proposed by Denker & Hafez (1975). Joshi & Murray (1974) and Rosenfeld & Joshi (1977 have implicated an oestrogen-dependent rat uterine-specific endopeptidase in zona lysis. Hoversland & Weitlauf (1981, 1982 have observed that the incidence of zona lysis in ovariectomized mice treated with oestradiol and progesterone follows a pattern similar to changes in concentrations of a uterine chymotrypsin-like enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Proteases which are present at high levels in the uterine epithelial cells and uterine secretions during the pre-attachment stage of pregnancy include an arylamidase which hydrolyses leucine ß-naphthylamide (mouse: Bergström, 1972;rabbit: van Hoorn & Denker, 1975;Denker, 1977) and an endopeptidase which acts on the specific substrate /V-acetyl tetra-L-alanine (rat: Joshi & Murray, 1974;Rosenfeld & Joshi, 1977). The endopeptidase, cathepsin D, has also been shown to be present in high concentrations in uterine epithelial cells during early pregnancy (rat : Elangovan & Moulton, 1980) and a chymotrypsinlike amidase has been reported in uterine flushings from ovariectomized animals receiving oestrogen and progesterone (mouse: Hoversland & Weitlauf, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…One approach is to administer the antisera intraluminally to the uterine horns of pregnant rats and to determine their effects on implantation (Rosenfeld & Joshi, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic development beyond the unilaminar blastocyst stage does not normally proceed until the blastocyst has freed itself from the zona peUucida (McLaren, 1974). The mechanism by which the shedding of the zona peUucida is regulated is not fully understood but apparently involves the action of proteolytic enzymes arising from the endometrium (McLaren, 1970; may also be involved in the process of lysis and this activity has been implicated in the initiation of implantation (Dickmann, 1969;Owers & Blandau, 1971;Denker, 1972;Andary, Dabich & Van Winkle, 1972;Pinsker et al, 1974;Rosenfeld & Joshi, 1977). In animals in which delayed implantation occurs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…& 1972;Notides, Hamilton & Rudolph, 1973;Pinsker, Sacco & Mintz, 1974;Joshi & Murray, 1974;Rosenfeld & Joshi, 1977). These enzymes seem to be controlled by the ovarian steroids(Dickmann, 1972;Surani, 1975).…”
mentioning
confidence: 99%